Sobre el trasllat de relíquies de Sant Cugat a Alsàcia i a Sant Denís, a prop de París, en època carolíngia - Pagès i Paretas, Montserrat (Miscel·lània litúrgica catalana, 2009)
This article deals with the transfert of relics of Saint Cucuphas to Leberau (Alsace), knonw from the will of Fulrad (777), adviser of the Carolingian kings and abbot of Saint-Denis, in France, who bequeathed them to the great Parisian abbey, where the martyrs altar was near the one devoted to Virgin Mary. The author revises the different theories that explain how the abbot might have adquired those prized relics, as well as the citation of the aniversary of the martyr in the liturgical sources of the time. It seems obvious that the diffussion of the cult of Saint Cucuphas in the monasteries of Mozarabic Spain as well as in the Carolingian court must be attributed to the primitive community of Sant Cugat del Vallès as a kind of propaganda in troubled times, after the Muslim invasion and before the Carolingian conquest, when the survival of the house was at risk. And that the second version of his passio must be related to that transfert of replics prior to 777.